Knowledge and Practice of Female Students Regarding Vitamin D Deficiency (International Journal of Nursing Education, 2020)
Background: Many studies evidenced that Vitamin D is an essential for good health especially it is associatedwith bone development. The deficiency usually may cause osteoporosis, muscle cramps and back pain.Objectives: The study aimed to determine the knowledge and the practices regarding vitamin D deficiencyamong the female students and associate the knowledge and selected demographic variables and correlateknowledge with the practice.Method: In descriptive research design, a cross sectional survey approach was used. Totally 190 studentswere selected randomly from King Faisal University who met inclusion criteria. The data was collected byusing structured questionnaire for assessing knowledge and checklist for practice.Results: Among 190 female students, many 62(32.6%) were in the age group of 20 and above. Majority ofthem 77(40.5%) were at final year, and 87(45.8%) were married. Regarding the overall level of knowledge97(51.1%) were having poor knowledge. About the practice, 80% of the students never had exposure tosunlight, 93.7% never engaged in outdoor physical activities. There was no significant association betweenknowledge and the selected demographic variables at the level of P<0.05. There was significant correlationbetween knowledge and their practices regarding the expose to sun light daily, engage in outdoor physicalactivities and wear abaya with niqab at p <0.001.Conclusion: Most of the female students were unaware of vitamin D sources and preventive measures ofits deficiency. Hence, the study recommends that, there should be more emphasis on awareness to improveknowledge and practices regarding vitamin D deficiency.Keywords: Vitamin D, Deficiency, Knowledge, Practice,